2021
DOI: 10.3390/su13179516
|View full text |Cite
|
Sign up to set email alerts
|

Potential and Economic Analysis of Solar-to-Hydrogen Production in the Sultanate of Oman

Abstract: Hydrogen production using renewable power is becoming an essential pillar for future sustainable energy sector development worldwide. The Sultanate of Oman is presently integrating renewable power generations with a large share of solar photovoltaic (PV) systems. The possibility of using the solar potential of the Sultanate can increase energy security and contribute to the development of the sustainable energy sector not only for the country but also for the international community. This study presents the hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…A potential economic study conducted to analyze solar to hydrogen production using PEM electrolysis was done for a different Wilayat in Oman. As the Al Ansab STP is located in Muscat, the solar PV energy result is 2,939 MWh/year which yielded 55,527 kg H 2 /year (Ahshan & Perea-Moreno, 2021). This can confirm the possibility of using the PV system with PEM technology to produce hydrogen in the Al Ansab STP.…”
Section: Figurementioning
confidence: 60%
“…A potential economic study conducted to analyze solar to hydrogen production using PEM electrolysis was done for a different Wilayat in Oman. As the Al Ansab STP is located in Muscat, the solar PV energy result is 2,939 MWh/year which yielded 55,527 kg H 2 /year (Ahshan & Perea-Moreno, 2021). This can confirm the possibility of using the PV system with PEM technology to produce hydrogen in the Al Ansab STP.…”
Section: Figurementioning
confidence: 60%
“…Regarding the voltage harmonics caused by switching the MOSFETs at high frequency, they are eliminated in the proposed topology by clamping the common mode voltage to a constant value, inputting DC bus voltage for C PV1 and the ground for C PV2 . For this reason, there is almost no leakage current, as shown in Equation (1). Furthermore, the input voltage has no limitations as long as the selected switches and other components in the inverter can tolerate that voltage.…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…Therefore, governments and national planning makers tend towards generating electricity based on renewable resources instead of conventional electricity resources. In 2020, 80% of the new installed capacity of electricity was from renewable resources, and 91% of that was wind and solar energy [1]. Moreover, in 2017 the nominal peak power installed worldwide of solar PV was almost 405 GW, and wind energy installation was approximately 540 GW [2].…”
Section: Introductionmentioning
confidence: 99%
“…A sensitivity analysis of the prices of various components showed that the price of the water electrolyzer has the most significant impact on the cost of producing green hydrogen [19]. Despite the different characteristics, the overall specific energy requirements of various alkaline electrolyzers (AE, AEL), PEM and solid oxide electrolyzer cell (SOEC) water electrolysis technologies are mainly similar.…”
Section: Literature Reviewmentioning
confidence: 99%